Arrangements for the Distribution of Song Royalties as Joint Property Are Regulated in Copyright Law - Yusuf, Nurullah Wahdania; Almoravid Dungga, Weny; Fazri Elfikri, Nurul (Estudiante Law Journal, 2024)
The purpose of this research is to be able to understand how the regulation of the distribution of song royalties as joint property according to Law Number 28 of 2014 concerning Copyright. The research method used in this research is the type of legal research used in this research is normative legal research. Normative legal research can also be referred to as doctrinal legal research. In this study, law is often conceptualized as what is written in laws and regulations (law in book) or law is conceptualized as rules or norms that are a benchmark for community behavior towards what is considered appropriate. The results of this study on the regulation of the distribution of song royalties as joint property in divorce cases are not specifically regulated in the Law. However, some of the provisions described in Law Number 28 of 2014 concerning Copyright can be a guide in this regard, especially Article 18 and Article 30 of the Copyright Law. These articles stipulate that after a period of 25 years, the economic rights to song creations that were previously transferred will return to the creator or performer. This is intended to protect the economic rights of the creator or performer over their work and prevent the transfer of economic rights that are permanent or indefinite to other parties.